Acetaminophen Poisoning and Risk of Acute Pancreatitis. Issue 29 (July 2015) - Chen, Sy-Jou; Lin, Chin-Sheng; Hsu, Chin-Wang; Lin, Cheng-Li; Kao, Chia-Hung; Okasha, Hussein.
<x xml:space="preserve">Abstract</x> Abstract The aim of this study was to assess whether acetaminophen poisoning is associated with a higher risk of acute pancreatitis. We conducted a retrospective cohort study by using the longitudinal population-based database of Taiwan's National Health Insurance (NHI) program between 2000 and 2011. The acetaminophen cohort comprised patients aged ≥20 years with newly identified acetaminophen poisoning (N = 2958). The comparison cohort comprised randomly selected patients with no history of acetaminophen poisoning. The acetaminophen and comparison cohorts were frequency matched by age, sex, and index year (N = 11, 832) at a 1:4 ratio. Each patient was followed up from the index date until the date an acute pancreatitis diagnosis was made, withdrawal from the NHI program, or December 31, 2011. Cox proportional hazard regression models were used to determine the effects of acetaminophen on the risk of acute pancreatitis. The risk of acute pancreatitis was 3.11-fold higher in the acetaminophen cohort than in the comparison cohort (11.2 vs 3.61 per 10, 000 person-years), with an adjusted hazard ratio of 2.40 (95% confidence interval, 1.29–4.47). The incidence rate was considerably high in patients who were aged 35 to 49 years, men, those who had comorbidities, and within the first year of follow-up. Acetaminophen poisoning is associated with an increased risk of acute pancreatitis. Additional prospective studies are necessary to verify how acetaminophen poisoning affects the risk of acute pancreatitis.